The Twitter Sentiment Analysis of Public Service Innovation: Pandawa BPJS Health Service - Yuliantini, Lisa Sophia; Sukarno, Mohamad (Universitas Muhammadiyah Yogyakarta, 2023)
This study is a sentiment analysis of the Pandawa government service innovation. Pandawa is an administrative service innovation using the WhatsApp application by the Health Social Security Administration Agency (BPJS) of the Republic of Indonesia. The Pandawa service innovation received many positive and negative responses from communities on the official Twitter account @BPJSKesehatanRI. This is interesting to study in measuring the quality-of-service innovation for the Pandawa based on sentiment analysis of the responses of the communities. This study aims to measure the quality of Pandawa service innovation based on sentiment analysis of the responses of the user community from BPJS Kesehatan. The research method in this study is descriptive qualitative by utilizing the Nvivo 12plus application in processing data. The data is then presented in the form of crosstab analysis and word cloud analysis. The primary data source for this study was obtained from comments from the Pandawa users on the official Twitter account @BPJSKesehatanRI and secondary data sources from literature studies, journals, and online mass media. The results of the study show that the Pandawa service innovation has not been implemented optimally. This is based on the results of sentiment data processing which shows a negative response of 70%, a positive 18%, and a neutral 12%. The data shows that the Pandawa is very slow in response, replied by robots, service is not complete, and it is considered that the Pandawa makes it difficult for the community to get service. The high results of negative sentiment in this study hope to become a reference for study material in improving the quality of the Pandawa service innovation so that users can optimally benefit from the ease of administrative services innovation based on the WhatsApp application.